Formulasi Arema Ralia (Aloe Vera Gel Mask With Extract Annredera Cordifolia) dan Tinjauan Aspek Kehalalannya - Sintia Ainus Shofa; Achmad Maulana (Jurnal DinamikA, 2020)
Aloe vera gel mask is one of the most popular cosmetic products in the world. In Indonesian sales, locally made it by contain alcohol (ethanol). Argued that ethanol is a type of alcohol can irritate quickly for sensitive skin. Alcohol is often perceived by some people as non halal. Based on the problems, innovation of Aloe Vera Gel mask for sensitive skins are made, named Arema Ralia (Aloe Vera Gel Mask with Extract of Annredera Cordifolia), and need to assess its halalness. The formulation does not involve the addition of ethanol, because the main ingredient contains several antibacterial compounds such as lignin, saponins, flavonoids, alkaloids, polyphenols, phenols. Arema Ralia is made by mixing annredera cordifolia and aloe vera with additional ingredients such as glycerin, NaCl, and water. The halal aspects of Arema Ralia need not be doubted. Alcohol content such as polyphenols and phenols in arema ralia is safe and beneficial for the skin. In addition, Polyphenols and phenols are not categorized as illicit alcohol according to the fatwa of MUI No. 11 of 2009, so that alcohol in Arema Ralia is halal.Keywords: Arema Ralia, Annredera Cordivolia, Halal, Aloe Vera, Mask